Desempenho fisiológico e superação de dormência em sementes de Brachiaria brizantha submetidas a tratamento químico e envelhecimento artificial - Cardoso, Eliana Duarte; Sa, Marco Eustaquio de [UNESP]; Haga, Kuniko Iwamoto [UNESP]; Silva Binotti, Flavio Ferreira da; Nogueira, Debora Cristiane [UNESP]; Valerio Filho, Walter Veriano [UNESP] (Univ Estadual Londrina, 2014)
The use of seeds of B. brizantha has increased, however, the physiological quality of seeds available to the producer is still a limiting factor for a good performance culture. The objective of this study was to evaluate the effects caused by chemical scarification, different periods of aging and priming on physiological quality and overcoming seed dormancy B. brizantha cv. MG-5 Victory. The seeds were subjected to chemical scarification-H2SO4 ( presence and absence), artificial aging periods ( zero, 24, 48, 72, 96, 120, 144 and 168 hours) at 41 degrees C and priming using the 0,2 KNO3 % ( presence and absence) for two hours at 25 degrees C, creating a completely randomized design in factorial 2x8x2, with four repetitions. The seeds were evaluated by testing germination and vigor. Chemical scarification is an effective method for breaking dormancy, but decreases the physiological seed. Overcoming seed dormancy B. brizantha occurs with the use of artificial aging for non-scarified and scarified seeds. Priming generally has no effect on the physiological quality and overcoming seed dormancy B. brizantha, however, it provides less loss of cellular constituents.
Physiological and performance in overcoming dormancy in seeds Brachiaria brizantha under artificial chemical treatment and aging
Keywords: cv. MG-5; chemical scarification; accelerated aging; priming and fisiological quality seeds